PERAN PEMERINTAHAN DESA DALAM PENGELOLAAN KEUANGAN DESA ALAI KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI TAHUN 2012 - Muhammad Basirruddin; Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Village in one form small community ,which is a small group of sedentary life ina region that remains. In the PP 72 of 2005 concerning the organization of theaffairs of the village where the village administration under the authority of thevillage funded from Budget village and help the Government in accordance withthe Ministry of Home Affairs letter No : 140/640SJ dated March 22, 2005 on theVillage Fund Allocation Guidelines (ADD ) of the District Government toGovernment village. Through Allocation Fund Village, the village has anopportunity to manage the development, administration and social villageautonomously. At the Law No. 32 Year 2004 on Regional Government, assertsthat "the granting of autonomy to the regional area Memepercepat directed to thewelfare of society through the creation of service improvement , empowermentand community participation . District Bylaw”. Meranti Islands No. 16 of 2011 onrural finance, "Financial management is a whole village planning,implementation, administration and accountability and financial control villages "( Article 3 ), while "the mayor is a village financial management authority ".(Article 13 ).The purpose of the study was to determine the role of government in the financialmanagement of rural villages, to find out the barriers faced by the village head inmanaging them. The method used was qualitative research, data collectiontechniques with interviews, conducted to determine the extent of VillageGovernment Role In Financial Management, literature study, a method of datacollection in order to obtain secondary data and observation which makeobservations directly on the object under study .Based on the results of the study authors, all financial management processesundertaken by the village government is in conformity with the applicableregulations, only the low level of education of human resources possessed by theapparatus and the low participation of Village Government Village Governmentrelated communities .Keywords : Role of Government , Management and Finance